Using Dictation Strategy in Teaching Listening Comprehension Achievements - Tri Nurhidayanti Tri; Masagus Sulaiman Sulaiaman; Dwi Rara Saraswaty Rara (Darussalam English Journal (DEJ), 2023)
This study aims to determine the effectiveness of the dictation strategy in improving students' listening comprehension achievements. The researchers applied a True Experimental research design in this study. There were 64 students in grade eight of SMP Dharma Bhakti Palembang who were involved as samples taken by purposive sampling technique. The researchers used pretest and posttest as research instruments to collect the data. To analyze the data, the researchers used a t-test, in line with the paired sample t-test and independent sample t-test.  The results showed that the alternative hypothesis (Ha) was accepted. The null hypothesis (Ho) was rejected, because t-obtained (3.430) was higher than t-table (2.045) and p output (0.01)<(0,05 which means that the dictation strategy was effective in teaching listening comprehension achievements to the Eighth Grade Students of SMP Dharma Bhakti Palembang.